Efektivitas Kurikulum Merdeka Dalam Meningkatkan Kemandirian Belajar di SD Negeri 6 Limboto Barat - Moh Fadlal Ladja; Muh Arif; Ritmon Amala (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effectiveness of the Merdeka Curriculum in enhancing independent learning among fourth-grade students at SD Negeri 6 Limboto Barat. The research focuses on three aspects: the effectiveness of curriculum implementation in fostering students’ independence, school strategies to optimize its application, and supporting and inhibiting factors. The study employed a qualitative approach, with data collected through observation, interviews, and documentation. The data were analyzed descriptively to provide a comprehensive picture of teaching practices and the involvement of schools and parents in supporting student independence. The findings show that the Merdeka Curriculum is fairly effective in cultivating independent learning. Students became more active, reflective, confident in expressing opinions, and responsible for their tasks. School strategies included initial ability mapping, continuous teacher training, teacher learning communities, and the use of digital technology. Supporting factors comprised teacher enthusiasm, adaptive leadership, adequate facilities, and parental involvement. Inhibiting factors included limited facilities, teachers’ adaptation challenges, heavy workloads, and uneven training. In conclusion, the Merdeka Curriculum effectively enhances students’ independent learning, although further mentoring and equitable support are still required.